2015
DOI: 10.1097/md.0000000000002332
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Co-Infections, and Outcomes of Viral Pneumonia in Adults

Abstract: Advanced technologies using polymerase-chain reaction have allowed for increased recognition of viral respiratory infections including pneumonia. Co-infections have been described for several respiratory viruses, especially with influenza. Outcomes of viral pneumonia, including cases with co-infections, have not been well described.This was observational cohort study conducted to describe hospitalized patients with viral pneumonia including co-infections, clinical outcomes, and predictors of mortality. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 32 publications
6
49
2
Order By: Relevance
“…The majority of patients with multiple viral infections had active malignancy. Fifty-eight of malignant patients were admitted to ICU following viral pneumonia (58). In another study, frequency of respiratory viral infections among children suffering from febrile neutropenia caused by cancer chemotherapy was surveyed by in-house real-time PCR.…”
mentioning
confidence: 99%
“…The majority of patients with multiple viral infections had active malignancy. Fifty-eight of malignant patients were admitted to ICU following viral pneumonia (58). In another study, frequency of respiratory viral infections among children suffering from febrile neutropenia caused by cancer chemotherapy was surveyed by in-house real-time PCR.…”
mentioning
confidence: 99%
“…Also, in almost one-third of the Simplexa™ positive samples, TAC detected Flu A and the presence of an additional pathogen. Respiratory co-infections, in particular, the association of Flu A with (an)other viral, bacterial or fungal pathogen(s), could be associated with longer hospital stay, a longer ICU stay and even higher mortality (Shah et al, 2016;Echenique et al, 2013;Crotty et al, 2015). Detecting these co-infections could have an important clinical impact.…”
Section: Discussionmentioning
confidence: 99%
“…7 Other investigators have suggested that detection of multiple respiratory viruses portends poor prognosis and may be a marker for occult immuncompromise. 8 Temporal pattern of symptoms Assessing the tempo of disease progression is also key to understanding the significance of a positive RVP. A long duration or interval since onset of URT symptoms followed by new or changed symptoms consistent with LRT or systemic infection suggests a pulmonary infiltrate in a patient with a positive NP or OP swab is more likely bacterial superinfection than primary viral pneumonia.…”
Section: Upper Versus Lower Respiratory Tract Diseasementioning
confidence: 99%
“…Up to 50% of patients with viral pneumonia may be immunocompromised. 8 Disseminated disease, including viremia, is much more likely in the severely immunocompromised.…”
Section: Immune Statusmentioning
confidence: 99%
See 1 more Smart Citation